Integrating Gender into Climate Change Adaptation Programs: A Research and Capacity Needs Assessment for Sub-Saharan Africa - Bryan, Elizabeth; Bernier, Quinn; Espinal, Marcia; Ringler, Claudia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
Research shows that paying attention to gender matters not only for the equity of climate change adaptation programs but also for their efficiency and effectiveness. Many organizations working to increase resilience to climate change with local communities also recognize the importance of gender yet the degree to which gender is integrated in project implementation is unclear. This study examines the extent to which organizations involved in climate change and resilience work are incorporating gender-sensitive approaches into their programs using data collected through a Knowledge, Attitudes and Practices (KAP) survey and Key Informant Interviews (KII) targeted at government agencies, local and international NGOs, and other practitioners. The results show that although organizations have access to research on climate change from various sources, more evidence is needed to inform gender integration into climate change adaptation programs across a range of local contexts. Moreover, large gaps exist in integrating gender into projects, particularly during project design. Lack of staff capacity on gender, lack of funding to support gender integration and socio-cultural constraints were identified as key barriers to gender integration by many respondents, particularly from government agencies. Increasing the capacity of organizations to carry out rigorous research and pay greater to the gender dimensions of their programs is possible through greater collaboration across organizations and more funding for gender-sensitive research.